Comparison Of Different Recovery Methods After An Acute Training Session On Aspartate Aminotransferase Activity And Some Hematological İndicators Of Blood İn Women Runners - Marıa Rahmanı Ghobadı; Seyed Ali Hoseini; Ghobad Hasanpour (Selcuk University, 2021)
The aim of this study was comparison of different recovery methods after an acute training session on aspartate aminotransferase activity and some hematological indicators of blood in women runners. The present study was applied and quasi-experimental. The statistical population of this study consisted of semi-professional female athletes in athletics (runners) in Tehran. Sampling was done by simple random sampling, so that after informing and inviting interested people and passing the preliminary stages, 30 people were selected from the runners as a research sample and these people were randomly divided into 3 groups of 10: group Active running recycling, passive recycling group and sports massage were included. They ran 200 meters on the track after a 2-hour training session of 25 seconds. In this study, one-way analysis of variance was used. The results of this study showed that there was no significant difference between the three types of recycling methods (inactive, double soft, massage) in changes in the factors of aspartate aminotransferase, iron. However, there was a significant difference between the three types of recycling methods (inactive, double soft, massage) in hematocrit changes. The recycling method can be used after the athletics competition.